Cadmium toxicity and sensitivity responses in Enterolobium contortisiliquum - Senhor, Daiane Franchesca (2023)
Soil contamination with heavy metals brings with it several environmental problems. Among these metals, cadmium (Cd) stands out as an extremely harmful element to plant development and may even cause possible loss or suppression of vegetation in various soils worldwide. Thus, it is necessary to identify tolerant species to reestablish the ecological conditions of the environment. The present study aimed to evaluate Cd tolerance in Enterolobium contortisiliquum seedlings by assessing the effects of Cd on morphophysiological and biochemical variables and determining its potential as a phytoremediator species. The experimental design was completely randomized with four replications. Five Cd concentrations (0, 25, 50, 75, and 100 µmol L-1) were assessed. At the end of the exposure period to the treatments, we measured photosynthetic, morphological (shoot and root dry weight and root morphology), and biochemical (concentration of photosynthetic pigments, hydrogen peroxide content, membrane lipid peroxidation, and guaiacol peroxidase and superoxide dismutase activity) variables in plants. Even with the activation of antioxidant enzymes, cadmium concentrations negatively affected the photosynthetic pigments and  photosynthetic rate of Enterolobium contortisiliquum, which reduced biomass production and photosystem functions, evidencing its sensitivity to excess Cd. Based on these characteristics, E. contortisiliquum seedlings can be used as a bioindicator for cadmium-contaminated areas.